Pengaruh Beban Kerja, Stres Kerja, dan Lingkungan Kerja terhadap Kinerja dengan Turnover Intention sebagai Mediasi pada Karyawan PT Farmasi XYZ dalam Masa Pandemi COVID-19 - Alicia Pricelda; Rudy Pramono (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
An organization or company needs quality human resources to create success. HRmanagement is important to note because it can affect the performance of HR. Severalfactors that need to be considered include work stress, workload, and the workenvironment, especially considering changing conditions such as during the COVID-19pandemic. In addition to performance, these factors can also affect the desire of HR towork in the company or what is known as turnover intention. The turnover intention ofHR will also affect performance. This study aims to examine the effect of workload, workstress, and work environment on performance with turnover intention as a mediation for PT XYZ pharmacy employees during the COVID-19 pandemic. This study uses aquantitative approach with a survey method on employees of PT XYZ. The number ofrespondents who collected as many as 160 with convenience sampling method. Dataanalysis technique using structural equation model (SEM) assisted by PLS softwareversion 3.3.2. The results of this study indicate that; work stress and workload have asignificant positive effect on turnover intention, while the work environment has anegative effect on turnover intention, workload and turnover intention have a significantnegative effect on performance, work environment has a significant positive effect onperformance, and work stress has an insignificant positive effect on performance, andturnover intention is a full mediation for the work stress variable, a partial mediationfor the workload, and not a mediation for the work environment.